2014
DOI: 10.1519/jsc.0b013e3182a1f757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Supplementation on the Physiological and Perceptual Responses to Prolonged Tennis Match Play

Abstract: Carbohydrate supplementation is a popular nutritional practice used in tennis to enhance physical capacities, motor-skill performance, and delay fatigue. However, the effects of carbohydrate supplementation on physiological and perceptual responses during tennis match play are not established. This double blind, randomized, placebo (PLA)-controlled crossover study was designed to determine the influence of carbohydrate supplementation (0.5 g·kg·h) on glycemia, salivary hormones (cortisol and testosterone) conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 38 publications
1
26
1
4
Order By: Relevance
“…In addition, they performed both trials at the euglycemic state. In agreement, it has been shown that a 3-h tennis match would not cause hypoglycemia in the subjects with adequate carbohydrate intake in the previous day (Gomes et al, 2014). However, the significant decline in perceptual-motor performance, indicated by the lower rate of balls hit to the correct direction, was still present after the simulated match in the PB trial.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, they performed both trials at the euglycemic state. In agreement, it has been shown that a 3-h tennis match would not cause hypoglycemia in the subjects with adequate carbohydrate intake in the previous day (Gomes et al, 2014). However, the significant decline in perceptual-motor performance, indicated by the lower rate of balls hit to the correct direction, was still present after the simulated match in the PB trial.…”
Section: Discussionsupporting
confidence: 65%
“…While age cannot be changed, fitness can, through conditioning. That can be obtained with a targeted training programme, including exercise (Smith, Sommer, and Starkoff 2013), rest, diet and supplementation (Gomes et al 2014;Orer and Gusel 2014). On the other hand, operator movement could be assisted with walking aids (Herr 2009) or minimised with new tools specifically designed for bringing the winch cable back to the loading point, without requiring that an operator walks back to the winch and pulls the cable all the way to the loading point.…”
Section: Discussionmentioning
confidence: 99%
“…Hornery et al 5 reported reductions in serve performance in a hypohydrated state, even though core temperatures remained below 39°C. Moreover, carbohydrate ingestion, in addition to the replinishment of fluid, is reported to be important during simulated tennis match-play 28. Given the prolonged durations of match-play, muscle glycogen availability or supply via exogenous glucose intake is likely to be a determining factor in the prevention of peripheral and central fatigue 5 28.…”
Section: Introductionmentioning
confidence: 99%